Dlaczego Augustyn napisał "Wyznania"? = Why did Augustine write the "Confessions"? - Królikowski, Janusz (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
Saint Augustine`s "Confessions", with its literary and spiritual specificity, set an important direction in Christian writing, which is still continued, and not only in Christian circles. Studies on the Bishop of Hippo discuss what prompted him to write this autobiographical work.
Keywords: Augustyn z Hippony (święty Kościoła katolickiego; 354-430); Augustyn z Hippony (święty Kościoła katolickiego; 354-430) - Wyznania; autobiografia; sławienie Boga; pokora; modlitwa; wędrówka duchowa; autobiography; Ancient rhetoric; praising God; humility; prayer; spiritual journey